PRAKTIK JUAL-BELI BARANG SECARA SISTEM SALAM DITINJAU DARI HUKUM ISLAM: Studi Kasus di Koperasi Serba Usaha Desa Kota Indonesia Desa Mekarjaya Kecamatan Gantar Kabupaten Indramayu - Aulia; Irvan Iswandi (Jurnal Penelitian Multidisiplin Ilmu, 2022)
This Undergraduate thesis discusses about the practice of goods buy and sell with Salam system reviewed from Islamic Law a case study at Various Business of Village and City in Indonesia, Mekarjaya Village, Gantar Sub District, Indramayu Regency. This Salam practice is a sale and purchase contract in which the goods order are suspended. However through the quality, quantity, type, and number of goods have been determined. The payment is conducted first when both parties agree to do the transaction. This undergraduate thesis aims to describe and explain the Islamic law review about Salam practice existed in various business cooperative of Village and City in Indonesia, Mekarjaya Village, Gantar Sub District, Indramayu Regency. Data collection techniques in this research were intervew and documentation. Data sources in this research were primary data namely the interview result with the apparatus, coordinator, and member of Various Business Cooperative of Village and City in Indonesia (KSU DESKOTIN) and secondary data namely documents, books, notes, and so on. Data analysis was conducted by using qualitative approach. Based on the research results obtained, it can be concluded that in salam practice at various business cooperative of Village and City in Indonesia, Mekarjaya Village, Gantar Sub District, Indramayu Regency the akd is valid because it has fulfilled the requirement and is in accordance with Islamic law. This As Salam akd prevails when the transaction between the coordinator and KSU DESKOTIN, even though not all coordinators during the transaction used al salam akd. Outside the transaction between the coordinator and KSU DESKOTIN, the akd is not al Salam but ba’i Mushowamah and ba’i Mua’zil.